Calvin's New Testament commentaries ; vol. 2 - Calvin, John, 1509-1564; Parker, T.H.L.; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1972)
Contents : v. 2 : Matthew, Mark and Luke : a harmony of the Gospels (v. II). Includes bibliographical references and indexes.
Keywords: Bible. N.T. Matthew -- commentaries; Bible. N.T. Mark -- commentaries; Bible. N.T. Luke -- commentaries